PLANTATION OF ENERGY PLANTS AS AN ELEMENT OF THE LANDSCAPE PROVIDING THE ECOSYSTEM SERVICES - Marián KOTRLA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Earth's ecosystems provide for humanity full range of benefits known as ecosystem goods and services. By the processing of information was used the methodology of Millennium Ecosystem Assessment (4 groups of ecosystem services). The paper assessed the first group of services - provisioning services with the possibility of using agricultural lands for growing energy plants. In the paper are evaluated the energy plant Miscanthus and Populus. The crop Miscanthus (covered 2010-2014) presented two genotypes. In 2012 (the third year of growing) has been reached the production of 24.85 t ha-1 (60% more than in 2011). In 2014 (the fifth year of growing) the crop reached production 28.60 t ha-1 of dry biomass. The plantations Miscantus x giganteus genotype planted the rhizomes are appeared productive. Fast-growing poplars Italian provenance, in the first three-year cycle in 2012 formed 51.47 t ha-1 of biomass. In 2014, the second year of the three-year harvest cycle average value of their biomass was 34.40 t ha-1. Based on an assessment of production above-ground organs monitored varieties of poplar are more productive varieties Monviso and Pegaso. Based on the evaluation of the ability of energy plant plantations (grasses genus Miscanthus and woody plant of the genus Populus) to produce enough above-ground biomass for energy use can be confirmed the high prevision service of this type of cultural ecosystem (agro-ecosystem).